EFFECTIVENESS OF BRAND COLLABORATIONS BETWEEN ANIMATION AND FASHION INDUSTRY - Nugraha, Zayyan Rafishafa Kabullah (PEOPLE: International Journal of Social Sciences, 2024)
This research discusses the impact of collaborations between fashion brands and animation studios amongst the customer. This phenomena has been intriguing for the researcher because recently in the last few years there have been countless collaborations between these brands. The brands have impacted the customers’ preferences and they purchase these collaboration items for many different reasons. The researcher started this research by mapping the background of these collaborations. After analyzing the background, the researcher started to find the topic or goal of this research which is finding the reasons behind why these collaborations are (most likely) to be successful. Following finding the focus on this research was a part of the beginning steps, the researcher started finding literature works related to my topic. Journals, academic articles, news articles and others that are related to fashion, brand collaboration, collaboration marketing, animation studios and so much more. These literatures helped me find the definition and information regarding aspects that are related to my research. After reading these literature works the researcher analyzed each of them and divided them into sections within my research. As the researcher has mentioned before, the researcher discussed the definition. Information, reasons, how it impacts other parts of the research or why they are related. After the literature review was finished the researcher continued to conduct a survey to receive first primary sourced data. The survey that was conducted consisted of questions related to the customers’ knowledge regarding anime, fashion brands, brand collaborations, their shopping preferences, their standard to shop a branded product and so much more. The survey received 151 respondents for my survey. From this survey the researcher received new information regarding my research and this definitely helped me in finding the reasons behind why customers or the market are interested in purchasing collaboration products between animation and fashion brands. The step after conducting the survey was analyzing the data that the researcher has collected. The researcher used descriptive and quantitative analysis from the graphs of the survey’s result. The researcher made a conclusion and analysis of each question’s answers. The answer with the highest amount in a question becomes the true answer or represents the majority of the population. After representing the survey’s data in the form of graphs and statistical analysis. The result of the survey and findings from the journal shows that there are various effects of brand collaborations towards the customers, whether they are from the animation series’ market or outside the market. There were also additional insights regarding people who are not interested in purchasing collaboration products, they gave their perspective about their reasonings on why they won’t be buying those items.